When the scientist presents an audio and video guide to science talks - Lebrun, Jean-Luc (World Scientific, 2010)
This book looks at the presenting scientist from a novel angle: the presenter-host. When scientists give a talk, the audience ("guests") expects the title of the talk to determine presentation content, they require understandable slides, and they demand visible and audible scientific authority. To each expectation corresponds a set of skills: personal (voice, host qualities, time control), technical (presentation tools and slide design), and scientific (Q&A, slide content). The author takes an original human factor view of the presentation delivery, in which the audience is easily distracted, rapidly forgetful, and increasingly impatient. Thus, insightful pointers are given on how to deliver the talk, how to craft the slides, and how to prevent the computer from rendering the presenting host-scientist into a "ghost". In addition, the book goes in-depth over the treatment of questions by examining the motives and style of the questioners, and advising on how best to answer to each type of questioner. The book comes with a DVD for audio and video examples, and includes essential PowerPoint and Keynote techniques that a presenter cannot live without
Includes index
(With DVD-ROM)
Keywords: Communication in science; Public speaking; Naturwissenschaften; Präsentation